VISUAL IDENTITY DESIGN FOR ROCK CLIMBING AS A PROMOTIONAL MEDIUM FOR MPA JONGGRING SALAKA - Mahardika, Restu Bintang; Sutrisno, Andika Agung (Warna Komunikasi, 2026)
Rock Climbing is becoming increasingly popular among university students. The Jonggring Salaka Nature Lovers’ Student Rock Climbing Division of Malang State University actively delegates athletes to various competitions. The division's existence is less well-known to the public. This occurs due to the lack of an independent visual identity. This study aims to design a representative visual identity as a promotional medium for the division. The researcher used a descriptive qualitative approach. The design process applies the Alina Wheeler model. This model includes research, strategy, identity design, contact points, and asset management stages. The researcher collected data through observation, interviews, and literature studies. The researcher used a SWOT analysis to formulate a design strategy. The design yields a new visual identity comprising a logo, Sport Lane typography, and a color palette of red, black, and white. The logo combines the shapes of Mount Semeru, a carabiner, a carmantel rope, and a star. The researcher applied these visual elements to various promotional media. These media include jerseys, water bottles, stickers, identity cards, and social media templates. The researcher also compiled a visual identity guidebook to maintain design consistency. This visual identity serves as a strategic solution to enhance the community's image and presence in the future.